A mechanism for tracking the water level - Muradov Khayot; Djalilov Anvar; Nurmatova Feruza (BIO Web of Conferences)
This research focuses on developing an advanced monitoring system for water levels in agricultural storage tanks, a critical component for ensuring reliable crop irrigation. In the context of increasing water scarcity and potential supply disruptions, enhanced monitoring of tank water levels becomes essential for sustainable farming practices. The proposed system addresses this need by providing farmers with precise, real-time data on water availability, enabling informed decision-making regarding irrigation scheduling and water resource allocation. The true innovation of this system lies in its ability to offer continuous visibility into tank water levels, empowering farmers to develop optimized water use strategies. By leveraging Internet of Things (IoT) technology through the Blynk application platform, the solution enables comprehensive tracking of both water levels and consumption patterns. The system incorporates threshold-based alert functionality to notify users when water reserves reach critically low levels. Experimental results demonstrate the successful implementation of this monitoring solution, with validation data confirming its accuracy in tracking water levels under various conditions. The Blynk interface has proven particularly effective in displaying real- time level information and generating timely alerts. This technological solution represents a significant step forward in agricultural water management, offering practical benefits for farmers operating in water- constrained environments.